Strategi Komunikasi Pemasaran Safin Pati Football Academy Dalam Meningkatkan Jumlah Peserta Didik Melalui Media Sosial nstagram - Syafilah, Saviratul (The Commercium, 2022)
This study aims to determine the marketing communication strategy of the Safin Pati Football Academy in increasing the quantity of new students through Instagram social media. Due to limitations in marketing due to the Covid-19 pandemic, Instagram social media is one of the alternative used in carrying out marketing communication strategies. This research uses a qualitative approach with a case study method. Data collection includes observations and interviews with involved parties. The results of the study indicate that Safin Pati emphasizes the uniqueness of the marketing mix of product on Instagram social media which includes the formation of student character. Marketing activities implemented by Safin Pati will be more optimal if it can develop the quality of its human resources, especially in the marketing sector.